Evaluación del sistema de electrocoagulación para disminuir la carga contaminante a escala de laboratorio (2019)
This work of degree was carried out to evaluate the method of electrocoagulation for the water treatment of the company PMP whose discharges are characterized by the content of organic load, it was found that these discharges had a value of fats and oils of 1264 mg / L, suspended solids of 17814 mg / L, sedimentable solids of 24007 mg / L, COD DE 85229 mg / L O2 and BOD of 12308 mg / L O2. After the diagnosis, the variables of the electrocoagulation method were defined, such as pH, current density, temperature, electrode material and reaction time. Two experiments were carried out, for the first experimentation it was necessary to do a preliminary test where the electrocoagulation method was evaluated in a time of 15 and 60 minutes with a voltage of 2V, this in order to identify if to remove the pollutant load of the PMP discharges is sufficient this time, the result of this preliminary test was not the expected for this reason it is decided to perform the first experimentation in a time of 1, 2, 3, 4, 5 and 6 hours, with a voltage of 2V and iron and aluminum electrodes, as a result it was obtained that the appropriate time for the removal of contaminants from the company is 4 hours obtaining a removal greater than 80%. When buying this result with the results found in the bibliography it is identified that the time is too high for the electrocoagulation method, for this reason a second experimentation was carried out where the method was evaluated using iron electrodes, a voltage of 2.7V, 7.7V and 12.6V and a time of 5, 15 and 30 minutes, was obtained as a result that for a voltage of 12.6 V and a time of 30 min was removed more than 90% for the parameters COD, suspended solids , sedimentables solids and fats and oils.